2009
DOI: 10.1080/03601270802708442
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing a New Short Screen for the Assessment of Older Women's PTSD Symptomatology

Abstract: It is difficult for busy health care providers to perform routine screening for older women’s posttraumatic stress symptomatology, due, at least partially, to a paucity of instruments specifically tested on such a population. To address this issue, in this preliminarily study we tested an abbreviated screen from the set of 20 items comprising the Distressing Event Questionnaire (DEQ; Kubany, Leisen, Kaplan, & Kelly, 2000) on a convenience sample of 94 ethnically diverse older women (ages 52–105). This new 5-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Scores on each of the five symptom-related items range from 0, that is, absent or did not occur, to 4, that is, present to an extreme or severe degree. Kubany, the first author of the DEQ, created the BPSSS (as further detailed in Lagana`& Schuitevoerder, 2009) at the Honolulu National Center for PTSD by selecting the five DEQ items that had the highest correlational values (ranging from 0.75 to 0.91) with the total DEQ scores obtained in two PTSD studies (described in Kubany et al, 2000). …”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores on each of the five symptom-related items range from 0, that is, absent or did not occur, to 4, that is, present to an extreme or severe degree. Kubany, the first author of the DEQ, created the BPSSS (as further detailed in Lagana`& Schuitevoerder, 2009) at the Honolulu National Center for PTSD by selecting the five DEQ items that had the highest correlational values (ranging from 0.75 to 0.91) with the total DEQ scores obtained in two PTSD studies (described in Kubany et al, 2000). …”
Section: Instrumentsmentioning
confidence: 99%
“…This list, developed by Lagana`, is a 10-item tool containing questions on demographic variables such as age, ethnicity, marital status, education, and stated income.The Brief Posttraumatic Stress Screening ScaleThe Brief Posttraumatic Stress Screening Scale (BPSSS;Lagana`& Schuitevoerder, 2009) is the new abbreviated version of the 20-item distressing event questionnaire (DEQ;Kubany, Leisen, Kaplan, & Kelly, 2000) that assesses PTSD symptomatology based on the DSM-IV-TR (American Psychiatric Association…”
mentioning
confidence: 99%
“…Perceived stress provides useful information beyond more objective measures of exposure to stressful events because it describes the individual’s interpretation of these stressors and his or her anticipated ability to negotiate such challenges. As such, research investigating the relationship between posttraumatic stress and more global perceived stress has found that increased posttraumatic stress disorder (PTSD) symptom severity and higher levels of perceived stress frequently co-occur in a variety of populations (e.g., Besser, Neria, & Haynes, 2009; Frasier et al, 2004; Laganá & Schuitevoerder, 2009; Qu et al, 2012). Perceived stress has also been identified as a specific risk factor in the development (Fincham, Altes, Stein, & Seedat, 2009; Haisch & Meyers, 2004) and experience (Besser et al, 2009) of PTSD.…”
mentioning
confidence: 99%
“…Given the estimated size of the problem, the topic of trauma in later life and associated resilience building has received surprisingly little attention (Anderson 2009; Hyer and Sohnle 2001). Researchers focusing on trauma in later life tend to focus on veterans, largely neglecting the impact of trauma on older women (Lagana 2009). Also, researchers largely ignore how unresolved traumatic events experienced earlier in life can impact on resilience later in life.…”
Section: Discussionmentioning
confidence: 99%